2015
DOI: 10.1111/php.12550
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Light on Alternative Splicing in Light‐Grown Plants

Abstract: Light modulates plant growth and development to a great extent by regulating gene expression programs. Here, we evaluated the effect of light on alternative splicing (AS) in light-grown Arabidopsis thaliana plants using high-throughput RNA sequencing (RNA-seq). We found that an acute light pulse given in the middle of the night, a treatment that simulates photoperiod lengthening, affected AS events corresponding to 382 genes. Some of these AS events were associated with genes involved in primary metabolism and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 31 publications
3
66
0
Order By: Relevance
“…This observation is in line with previous studies showing extensive and regulated AS for the pre-mRNAs of many splicing factors (Reddy and Shad Ali, 2011;Syed et al, 2012;Wachter et al, 2012;Reddy et al, 2013;Staiger and Brown, 2013;Mancini et al, 2016), which allows quantitative gene control by coupling to NMD (see above) but might also increase their functional diversity. Interestingly, among our candidates was RRC1, a putative splicing factor that had previously been identified as a component of PHYB signaling (Shikata et al, 2012a;Shikata et al, 2012b showed that the C-terminal arginine/serine-rich (RS) domain of RRC1 is required for its function in PHYB signaling (Shikata et al, 2012a;Shikata et al, 2012b).…”
Section: Light-dependent As Defines Expression Of Splicing Factors Ansupporting
confidence: 80%
See 4 more Smart Citations
“…This observation is in line with previous studies showing extensive and regulated AS for the pre-mRNAs of many splicing factors (Reddy and Shad Ali, 2011;Syed et al, 2012;Wachter et al, 2012;Reddy et al, 2013;Staiger and Brown, 2013;Mancini et al, 2016), which allows quantitative gene control by coupling to NMD (see above) but might also increase their functional diversity. Interestingly, among our candidates was RRC1, a putative splicing factor that had previously been identified as a component of PHYB signaling (Shikata et al, 2012a;Shikata et al, 2012b showed that the C-terminal arginine/serine-rich (RS) domain of RRC1 is required for its function in PHYB signaling (Shikata et al, 2012a;Shikata et al, 2012b).…”
Section: Light-dependent As Defines Expression Of Splicing Factors Ansupporting
confidence: 80%
“…Comparisons of AS profiles for light-versus dark-grown rice seedlings using microarrays (Jung et al, 2009) and for A. thaliana seedlings with a high-resolution reverse transcription polymerase chain reaction (RT-PCR) panel (Simpson et al, 2008) indicated that light-mediated changes in AS patterns might affect the expression of numerous genes. This notion was further supported by recent studies using RNA sequencing (RNA-seq) to deduce light-regulated AS patterns in a transcriptome-wide manner in the moss Physcomitrella patens (Wu et al, 2014), etiolated A. thaliana seedlings (Shikata et al, 2014), and light-grown A. thaliana plants (Mancini et al, 2016). Interestingly, Wu et al (2014) and Shikata et al (2014) reported PHY signaling acting upstream of light-regulated AS.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations